Late adverse reactions to intravascular iodinated contrast media - Webb, Judith A.; Stacul, Fulvio; Thomsen, Henrik S.; Morcos, Sameh K.; Members of the Contrast Media Safe (European radiology, 2003)
Late adverse reactions to intravascular iodinated contrast media are defined as reactions occurring 1 h to 1 week after contrast medium injection. They have received increasing interest over the past decade, but their prevalence remains uncertain and their pathophysiology is not fully understood. The Contrast Media Safety Committee of the European Society of Urogenital Radiology decided to review the literature and to issue guidelines. An extensive literature search was carried out and summarized in a report. Based on the available information, simple guidelines have been drawn up. The report and guidelines were discussed at the 8th European Symposium on Urogenital Radiology in Genoa. Late adverse reactions after intravascular iodinated contrast medium include symptoms such as nausea, vomiting, headache, itching, skin rash, musculoskeletal pain, and fever. A significant proportion of these reactions is unrelated to the contrast medium; however, allergy-like skin reactions are well-documented side effects of contrast media with an incidence of approximately 2%. Late reactions appear to be commoner after non-ionic dimers. The majority of late skin reactions after contrast medium exposure are probably T-cell-mediated allergic reactions. Patients at increased risk of late skin reactions are those with a history of previous contrast medium reaction and those on interleukin-2 treatment. Most skin reactions are self-limiting and resolve within a week. Management is symptomatic and similar to the management of other drug-induced skin reactions.